Combining Archival Data and Program-Generated Electronic Records to Improve the Usefulness of Efficacy Trials in Education: General Considerations and an Empirical Example. Issue 4 (2nd October 2019) - White, Mark C.; Rowan, Brian; Hansen, Ben; Lycurgus, Timothy
Abstract: There is growing pressure to make efficacy experiments more useful. This requires attending to the twin goals of generalizing experimental results to those schools that will use the results and testing the intervention's theory of action. We show how electronic records, created naturally during the daily operation of technology-based interventions, contain the information needed to attend to these twin goals. These records allow researchers to define the population of schools considering adoption of an intervention and to plan an experiment to generalize to these schools. They also allow researchers to identify schools likely to fully implement the intervention, such that the theory of action can be properly tested. Designing experiments to address these goals involves many tradeoffs and prioritizing the different purposes of the planned experiment. We discuss these challenges, linking experimental purposes with design decisions.